Simplify the expression:

(6q + 1)(3) =

11 answers

To simplify the expression \((6q + 1)(3)\), you can distribute the \(3\) across the terms inside the parentheses:

\[ (6q + 1)(3) = 6q \cdot 3 + 1 \cdot 3 \]

Calculating each term, you get:

\[ 6q \cdot 3 = 18q \] \[ 1 \cdot 3 = 3 \]

Now, combine these results:

\[ 18q + 3 \]

So, the simplified expression is:

\[ \boxed{18q + 3} \]

Simplify the expression:

2(2 + m) =

To simplify the expression \(2(2 + m)\), you can distribute the \(2\) across the terms inside the parentheses:

\[ 2(2 + m) = 2 \cdot 2 + 2 \cdot m \]

Calculating each term:

\[ 2 \cdot 2 = 4 \] \[ 2 \cdot m = 2m \]

Now, combine these results:

\[ 4 + 2m \]

So, the simplified expression is:

\[ \boxed{4 + 2m} \]

Simplify the expression:

(1 + x)(5) =

To simplify the expression \((1 + x)(5)\), you distribute the \(5\) across the terms inside the parentheses:

\[ (1 + x)(5) = 1 \cdot 5 + x \cdot 5 \]

Calculating each term, you get:

\[ 1 \cdot 5 = 5 \] \[ x \cdot 5 = 5x \]

Now, combine these results:

\[ 5 + 5x \]

So, the simplified expression is:

\[ \boxed{5 + 5x} \]

Simplify the expression:

2(3 + 6k)

To simplify the expression \(2(3 + 6k)\), you distribute the \(2\) across the terms inside the parentheses:

\[ 2(3 + 6k) = 2 \cdot 3 + 2 \cdot 6k \]

Calculating each term gives:

\[ 2 \cdot 3 = 6 \] \[ 2 \cdot 6k = 12k \]

Now, combine these results:

\[ 6 + 12k \]

So, the simplified expression is:

\[ \boxed{6 + 12k} \]

Simplify the expression:

–3(5 − 4c)

To simplify the expression \(-3(5 - 4c)\), you distribute the \(-3\) across the terms inside the parentheses:

\[ -3(5 - 4c) = -3 \cdot 5 + (-3) \cdot (-4c) \]

Calculating each term gives:

\[ -3 \cdot 5 = -15 \] \[ -3 \cdot (-4c) = 12c \]

Now, combine these results:

\[ -15 + 12c \]

So, the simplified expression is:

\[ \boxed{-15 + 12c} \]

Simplify the expression:

5(–2 − 7d)

To simplify the expression \(5(-2 - 7d)\), you will distribute the \(5\) across the terms inside the parentheses:

\[ 5(-2 - 7d) = 5 \cdot (-2) + 5 \cdot (-7d) \]

Calculating each term gives:

\[ 5 \cdot (-2) = -10 \] \[ 5 \cdot (-7d) = -35d \]

Now, combine these results:

\[ -10 - 35d \]

So, the simplified expression is:

\[ \boxed{-10 - 35d} \]